Resin composition and application thereof, semiconductor device and method for manufacturing the same

By using a chemical connection with the surface of the small molecule in the resin composition and the surface of the pattern, the problem of too much complication of pattern thin film in the existing technologies has been solved. Sexuality meets the requirements of high -resolution patterns.

CN118994990BActive Publication Date: 2025-01-28ZHUHAI CORNERSTONE TECH CO LTD
View PDF 3 Cites 0 Cited by

Patent Information

Application Number
CN202411477207.8
Authority / Receiving Office
CN · China
Patent Type
Patents(China)
Current Assignee / Owner
Filing Date
2024-10-22
Publication Date
2025-01-28
Estimated Expiration
2044-10-22

AI Technical Summary

Technical Problem

The crosslinking reaction between the macromolecular crosslinking agent and the surface of the patterned film in existing patterned microscopic materials causes the shrinkage of the patterned film to be too large, making it difficult to meet the requirements of high-resolution patterning.

Method used

Provide a resin composition, including resin, coupling agent and non -water organic solvent. The coupling agent is small molecule titanate, moltate, or aluminate. The resin contains the first duplicate of the reaction group with a reaction group with a side chain The second duplicate unit of the unit and the non-reaction group, the mass of the coupling agent accounts for 1%-30%of the quality of the resin. The resin composition has a chemical connection with the surface of the pattern thin film under heating conditions to achieve moderate pattern size contraction.

Benefits of technology

By using the resin composition, the size shrinkage of the pattern film can be controlled within an appropriate range to ensure the requirements of the average and high -resolution patternization of the graphic size, while reducing the graphic adhesion probability.

✦ Generated by Eureka AI based on patent content.

Smart Images

  • Figure CN118994990B_ABST
    Figure CN118994990B_ABST
Patent Text Reader

Abstract

The present application embodiment provides a resin composition and its application, a semiconductor device and its manufacturing method. The resin composition can be used for pattern size scaling of patterned film, which includes resin, coupling agent and non-aqueous organic solvent, the coupling agent includes one or more of titanate, zirconate, aluminate, the resin includes a first repeating unit with at least one of hydroxyl and carboxyl in the side chain, and a second repeating unit without hydroxyl or carboxyl in the side chain, and the mass of the coupling agent is 1%-30% of the mass of the resin. The above-mentioned resin composition can achieve a moderate and uniform reduction in the pattern spacing of the patterned film, meeting the requirements of the semiconductor field for high-resolution patterning.
Need to check novelty before this filing date? Find Prior Art

Description

Technical Field

[0001] The present application relates to the field of patterning technology, and in particular to a resin composition and application thereof, a semiconductor device and a method for manufacturing the same. Background Art

[0002] As the integration of semiconductor integrated circuits continues to increase, the requirements for the critical dimension (CD) of the chip pattern structure are also continuously reduced, the exposure wavelength used in the patterning process is getting shorter and shorter, and the cost of exposure equipment is also increasing. Without introducing new high-cost exposure equipment, achieving pattern shrinkage of patterned thin films on substrates for manufacturing integrated circuits can improve the resolution of the functional layer pattern obtained thereby and significantly reduce manufacturing costs.

[0003] Among them, graphic miniaturization materials are often used to coat the surface of patterned films, which usually contain resins and macromolecular crosslinking agents. Under heating conditions, the macromolecular crosslinking agent can crosslink and cure the resin with carboxyl groups on the surface of the patterned film, thereby increasing the film thickness and graphic sidewalls of the patterned film, and reducing the size of through holes or line gaps in the patterned film, thereby forming a finer pattern. However, the crosslinking reaction between the macromolecular crosslinking agent and the surface of the patterned film in the existing graphic miniaturization materials usually causes the size of the patterned film to shrink too much, which may cause problems such as graphic bridging under the high-resolution patterning requirements of advanced nodes. Summary of the invention

[0004] In view of this, the embodiments of the present application provide a resin composition and its application, a semiconductor device and its manufacturing method. The resin composition can make the patterned film have an appropriate dimensional shrinkage and a uniform shrinkage degree to meet the requirements of high-resolution patterning in the field of semiconductor devices.

[0005] Specifically, the first aspect of an embodiment of the present application provides a resin composition for scaling the pattern size of a patterned film, the resin composition comprising a resin, a coupling agent and a non-aqueous organic solvent, wherein the coupling agent comprises one or more of titanate, zirconate and aluminate, the resin comprises a first repeating unit having a side chain with a reactive group that can react with the coupling agent, and a second repeating unit having a side chain without the reactive group, the reactive group comprises a hydroxyl group and / or a carboxyl group, and the mass of the coupling agent is 1%-30% of the mass of the resin.

[0006] The resin composition is coated on the surface of the patterned film. Under heating conditions, the bridging effect of the small molecule coupling agent can be used to achieve chemical connection between the resin in the resin composition and specific reactive groups (such as carboxyl, hydroxyl, etc.) on the surface of the patterned film, thereby increasing the size of the pattern sidewalls of the patterned film. After removing the resin composition material not connected to the surface of the patterned film, the spacing between the patterns can be moderately and evenly reduced, the probability of pattern adhesion is reduced, the uniformity of the pattern size is ensured, and the requirements of high-resolution patterning can be met.

[0007] In some embodiments of the present application, the chemical formula of the titanate includes TiL4, the chemical formula of the zirconate includes ZrL4, and the chemical formula of the aluminate includes AlL3, and each L is independently selected from C 2-8 One of an alkoxy group, a benzyloxy group, a triethanolamine group, an acetylacetonate group, and an ethyl acetoacetate group.

[0008] In some embodiments of the present application, the coupling agent further comprises orthosilicate. The chemical formula of the orthosilicate comprises Si(OR)4, and each R is independently selected from methyl, ethyl, n-propyl, isopropyl, n-butyl, 2-methoxyethyl, and benzyl each time it appears. Orthosilicate is also a small molecule coupling agent, which can play a similar effect of bridging the resin and the patterned film surface with the above-mentioned titanate, zirconate, aluminate, etc.

[0009] In the embodiment of the present application, in the resin composition, the total mass proportion of the coupling agent and the resin is 0.5wt%-5wt%. This can ensure that the graphic sidewall of the patterned film coated with the resin composition can be effectively thickened without causing waste of the resin composition.

[0010] In some embodiments of the present application, the molar proportion of the first repeating unit in all repeating units of the resin is 30%-80%. Controlling the molar proportion of the active repeating units containing hydroxyl and / or carboxyl groups in the resin within a suitable range is beneficial for the resin to have a higher solubility in non-aqueous organic solvents and for the above-mentioned resin composition containing the resin to effectively thicken the patterned film.

[0011] In some embodiments of the present application, the first repeating unit comprises the structure represented by the following formula (I-1) and / or formula (I-2):

[0012] (Ⅰ-1) (Ⅰ-2)

[0013] Wherein, R1 and R2 are independently selected from hydrogen atoms, halogen atoms, methyl groups or halogenated methyl groups; L1 is independently selected from single bonds, *-COO-, or *-CONH- each time it occurs, and the * end is connected to the main chain carbon atom of formula (Ⅰ-1); L2 is independently selected from *-COO-, or *-CONH- each time it occurs, and the * end is connected to the main chain carbon atom of formula (Ⅰ-2); Z includes at least one of -OH and -COOH; R3 includes a substituted alkyl group including at least one of -OH and -COOH.

[0014] In some embodiments of the present application, the second repeating unit includes one or more repeating units derived from styrene substances that do not contain hydroxyl groups and carboxyl groups, alkyl acrylates, and alkyl methacrylates.

[0015] In the embodiment of the present application, the weight average molecular weight of the resin is in the range of 1000-20000. This can ensure that the resin has high solubility in the above-mentioned resin composition, and the resin has an appropriate number of first repeating units that can be chemically bonded with the coupling agent to effectively thicken the patterned film. In some embodiments, the weight average molecular weight of the resin is in the range of 4000-10000.

[0016] In the embodiment of the present application, the non-aqueous organic solvent includes one or more of an alcohol solvent and an ether solvent. These non-aqueous solvents are not likely to dissolve and damage the patterned film in contact with the resin composition, and can make the above-mentioned resin and coupling agent dissolve well therein.

[0017] In some embodiments of the present application, the alcohol solvent includes one or more of methanol, ethanol, n-propanol, isopropanol, n-butanol, sec-butanol, and 4-methyl-2-pentanol; the ether solvent includes one or more of n-butyl ether, diisoamyl ether, and dipropylene glycol dimethyl ether.

[0018] The second aspect of the embodiment of the present application provides the use of the resin composition as described in the first aspect of the embodiment of the present application in reducing the critical dimension of the pattern. The application can specifically be to reduce the pattern spacing of the patterned film. With the patterned film with reduced pattern spacing, a functional layer pattern with a smaller critical dimension and higher resolution can be obtained, thereby obtaining a semiconductor device with a higher degree of integration.

[0019] A third aspect of an embodiment of the present application provides a method for manufacturing a semiconductor device, comprising:

[0020] (1) Providing a substrate having a patterned film on its surface; the surface of the patterned film has at least one of a hydroxyl group and a carboxyl group;

[0021] (2) applying the resin composition described in the first aspect of the embodiment of the present application to the surface of the patterned film to form a resin film, and heating the resin film to react with the portion of the resin film in contact with the patterned film;

[0022] (3) The unreacted resin film is removed by a cleaning solution to obtain a fine patterned film with reduced pattern spacing on the substrate.

[0023] The manufacturing method of the above-mentioned semiconductor device, by adopting the above-mentioned resin composition of the embodiment of the present application as the pattern shrinkage material, can achieve a moderate reduction in the pattern spacing of the formed patterned film, obtain a fine pattern with a smaller critical dimension at a lower cost, and ensure that the defects of the obtained pattern are small, which is conducive to the development of ultra-high integration of semiconductor devices.

[0024] In some embodiments of the present application, after obtaining a fine patterned film with reduced pattern spacing in step (3), the method may further include: transferring the pattern of the fine patterned film to a substrate to obtain a patterned substrate. Further, after obtaining the patterned substrate, the method may further include: forming a structure required for a semiconductor device on the patterned substrate.

[0025] The embodiment of the present application also provides a semiconductor device, which is manufactured using the manufacturing method described in the third aspect of the embodiment of the present application. BRIEF DESCRIPTION OF THE DRAWINGS

[0026] Figure 1 A schematic diagram showing the use of the resin composition of the present application to reduce the pattern spacing of a patterned film.

[0027] Figure 2 (a) shows a top view of the contact hole pattern template used in the present application under a scanning electron microscope. Figure 2 (b), (c), and (d) respectively show the top views of the contact hole pattern template after the pattern shrinkage is carried out by the resin composition of Example 1 of the present application at heating temperatures of 100° C., 120° C., and 150° C., respectively. Figure 2 (e) shows a top view of the contact hole pattern template after the contact hole pattern template is subjected to pattern shrinkage at a heating temperature of 150° C. using the resin composition of Comparative Example 1.

[0028] Figure 3 (a) shows a scanning electron microscope top view of the line pattern template used in this application, Figure 3 (b), (c), and (d) respectively show the scanning electron microscope top views of the line pattern template after the pattern shrinkage is carried out by the resin composition of Example 2 of the present application at heating temperatures of 100°C, 120°C, and 135°C, respectively. DETAILED DESCRIPTION

[0029] The embodiments of the present application will be described below in conjunction with the drawings in the embodiments of the present application.

[0030] In advanced semiconductor manufacturing processes, the patterning process generally includes the following steps: (1) coating a patterning composition (such as a chemically amplified photoresist including a base resin and a photoacid generator) on a substrate to form a patterned material film layer; (2) selectively exposing the patterned material film layer through an exposure source through a mask with a predetermined pattern, causing the photoacid generator in the exposure area to decompose and generate acid; in the baking process after exposure, the photoacid catalyzes the deprotection of the acid-labile protecting groups in the base resin in the exposure area, thereby increasing the polarity of the base resin in the exposure area, thereby producing a difference in the solubility of the developer in the exposure area and the unexposed area; (3) after exposure and baking, the patterned material film layer is developed with a developer, leaving a patterned film with the same or opposite pattern as the mask on the substrate. The substrate can be selectively etched using this patterned film as a mask. Among them, if the exposed area of ​​the patterned material is removed by the developer (such as an aqueous solution of tetramethylammonium hydroxide) during development, the development can be called "positive development", and the photoresist pattern left on the substrate is a positive pattern, which is basically the same as the pattern of the exposure mask; if the unexposed area of ​​the patterned material is removed by the developer (such as an organic solvent such as n-butyl acetate) during development, the development can be called "negative development", and the photoresist pattern left on the substrate is a negative pattern, which is basically complementary to the pattern of the exposure mask.

[0031] Regardless of whether it is positive development or negative development, the pattern surface of the above-mentioned patterned film left on the substrate has functional groups such as carboxyl and / or hydroxyl groups generated by the deprotection of the acid-labile protective groups (generally, the positive pattern only has these functional groups on the pattern surface, and the negative pattern has these functional groups inside and on the surface), and these functional groups provide reaction sites that can be used by the pattern miniaturization material. Common pattern miniaturization materials usually contain resins and macromolecular crosslinking agents. The pattern miniaturization material is coated on the surface of the above-mentioned patterned film. Under heating conditions, the crosslinking agent in the composition can cause the resin to undergo a crosslinking and curing reaction with the carboxyl and / or hydroxyl groups on the surface of the patterned film, so that the pattern of the patterned film becomes wider. After removing the pattern miniaturization material that has not been crosslinked and cured with the patterned film, a patterned film with a shrunk pattern spacing (such as a reduced line gap, a reduced through-hole size, etc.) is obtained. The resolution of the deposited material pattern (such as metal interconnection lines, trench filling structures) obtained by filling the pattern gap, or the functional layer pattern obtained by etching with it as a mask is greater than the pattern obtained based on the initial patterned film.

[0032] However, the cross-linking reaction between the macromolecular cross-linking agent in the existing graphic miniaturization material and the surface of the patterned film usually causes a large size shrinkage of the patterned film. For the initial patterned film with a high resolution, too large a size shrinkage may cause problems such as pattern bridging, thereby reducing the quality of the pattern. In order to solve this technical problem, the embodiment of the present application provides a resin composition that can be used as a graphic miniaturization material, and the small molecule coupling agent therein can achieve an appropriate degree of size shrinkage of the patterned film and ensure the uniformity of the graphic size to meet the requirements of high-resolution patterning.

[0033] An embodiment of the present application provides a resin composition for scaling the pattern size of a patterned film, wherein the resin composition includes a resin, a coupling agent and a non-aqueous organic solvent, wherein the coupling agent includes one or more of titanate, zirconate and aluminate, and the resin includes a first repeating unit having a side chain with a reactive group that can react with the coupling agent, and a second repeating unit having a side chain without the reactive group, wherein the reactive group includes a hydroxyl group and / or a carboxyl group, and the mass of the coupling agent is 1%-30% of the mass of the resin.

[0034] The coupling agent contained in the above-mentioned resin composition is not a high molecular polymer, but a small molecule organic-inorganic hybrid coupling agent, which has a central metal atom (such as titanium, zirconium, aluminum) and multiple organic groups (such as substituted or unsubstituted alkoxy groups). Under heating conditions, by utilizing the bridging effect of the above-mentioned small molecule coupling agent, a chemical thickening layer can be formed on the surface of the patterned film by means of the connection between the central metal atom and the above-mentioned resin with carboxyl and / or hydroxyl groups and the patterned film with specific reactive groups (such as carboxyl, hydroxyl, etc.) on the surface, thereby increasing the thickness of the patterned film and the width of the pattern (i.e., the thickness of the side wall of the pattern). After removing the resin and coupling agent not connected to the surface of the patterned film, the appropriate reduction of the pattern spacing distance is achieved. In addition, since the above-mentioned coupling agent is a small molecule substance, the distance between the surface layer of the patterned film and the resin to which it is bonded is shortened by the coupling of the coupling agent, so that the thickness of the above-mentioned chemical thickening layer is relatively small, but the density is large and the thickness is more uniform, thereby improving the uniformity of the shrinkage amplitude of the key dimensions of the patterned film. In addition, the resin is controlled to contain the above two repeating units at the same time, and it can have a certain solubility in non-aqueous organic solvents such as alcohol solvents and ether solvents, ensuring that the resin composition is not easy to precipitate and is easy to apply; and the mass of the coupling agent is controlled to be 1-30% of the mass of the resin, which can ensure that the above resin composition has an appropriate content of the coupling agent to ensure that it can fully connect the resin with the surface of the patterned film to effectively thicken the patterned film, and will not cause material waste of the coupling agent and affect its solubility in the resin composition. Therefore, the use of the above resin composition can appropriately reduce the critical size of the patterned film, and the degree of size reduction is relatively uniform, meeting the requirements of high-resolution patterning, and can also produce a patterned film with a smaller critical size without replacing a new exposure device with a shorter wavelength.

[0035] Wherein, for a patterned film having a contact hole pattern, the scaling of the pattern size may refer to the reduction of the hole diameter. For a patterned film having a line pattern, the scaling of the pattern size may refer to the reduction of the line spacing.

[0036] It should be noted that the above-mentioned resin composition of the present application is not a photosensitive resin composition (or "photoresist") for forming a patterned film, so the resin composition of the present application does not contain an acid generator (such as a photoacid generator or a thermal acid generator) or a photoinitiator.

[0037] Specifically, in the resin composition, the mass of the coupling agent may be 2%, 5%, 8%, 10%, 12%, 15%, 16%, 12%, 15%, 16%, 18%, 20%, 22%, 25%, or 28% of the mass of the resin. In some embodiments, the mass of the coupling agent may be 10%-25% of the mass of the resin.

[0038] In the present application, the structure of the above titanate, zirconate, and aluminate is not specifically limited, as long as the coupling effect can be achieved. Among them, the titanate, zirconate, and aluminate may have at least one central metal atom.

[0039] In some embodiments, the chemical formula of the titanate includes TiL4. The chemical formula of the zirconate includes ZrL4. The chemical formula of the aluminate includes AlL3. Each L is independently selected from C 2-8 One of the group consisting of an alkoxy group (such as ethoxy, n-propoxy, isopropoxy, n-butoxy, 2-ethylhexyloxy, etc.), a benzyloxy group (i.e., benzyloxy), a triethanolamine group, an acetylacetonate group, and an ethyl acetoacetate group.

[0040] Among them, the structure of 2-ethylhexyloxy is: The structure of the benzyloxy group is -O-CH2C6H5, which is a methoxy group substituted by a phenyl group. The structure of the triethanolamine group can be represented as , this group is essentially a substituted alkoxy group, that is, an ethoxy group substituted by N,N-bis(hydroxyethyl). Substituted or unsubstituted alkoxy groups can be converted into -OH under certain conditions, and the M-OH group (M represents the central metal atom) in the coupling agent is used to achieve the connection between it and the resin and patterned film with carboxyl and / or hydroxyl groups. Among them, the structure of the acetylacetonate group can be expressed as: The structure of ethyl acetoacetate can be expressed as: The acetylacetonate group or ethyl acetoacetate group can coordinate with metal atoms such as Ti, Zr, and Al, but its binding ability with metal atoms is not as strong as that of -COOH or -OH. Under certain conditions, the acetylacetonate group or ethyl acetoacetate group can be replaced by -COOH or -OH in the above-mentioned resin or patterned film to achieve connection between the resin and the patterned film surface.

[0041] As for titanate coupling agents, in some cases, tetraethyl titanate (Ti(OCH2CH3)4), tetra-n-propyl titanate (Ti(OCH2CH2CH3)4), tetraisopropyl titanate (structural formula: ), tetrabutyl titanate (Ti(OCH2CH2CH2CH3)4), bis(acetylacetonato) diisopropyl titanate (structural formula is or ), diisopropyl di(triethanolamine) titanate (structural formula: In some other embodiments, the titanate may also be hexabutoxy-μ-titanium (IV) oxide (structural formula: ).

[0042] As the zirconate coupling agent, one or more of tetraethyl zirconate, tetra-n-propyl titanate, tetraisopropyl zirconate, tetra-n-butyl zirconate and the like may be cited.

[0043] Examples of the aluminate coupling agent include triethyl aluminate, triisopropyl aluminate, tributyl aluminate, tribenzyl aluminate, aluminum triacetylacetonate, , bis(acetylacetonato)isopropylaluminate , (acetylacetonato) diisopropylaluminate , (ethyl acetoacetate) diisopropoxyaluminate wait.

[0044] In some embodiments of the present application, for titanate or zirconate, at least two of the four Ls are substituted or unsubstituted alkoxy groups, and further, the four Ls may be independently selected from substituted or unsubstituted alkoxy groups. For aluminate, at least two of the three Ls are substituted or unsubstituted alkoxy groups, and further, the three Ls are independently selected from substituted or unsubstituted alkoxy groups. Such titanate or zirconate, or aluminate has a strong coupling ability, which can be used to achieve the function of connecting the resin in the resin composition with the surface of the patterned film, and better meet the requirements of establishing a stable chemical thickening layer of appropriate thickness on the surface of the patterned film.

[0045] The following takes titanate with the chemical formula TiL4 (L is a substituted or unsubstituted alkoxy group -OR) as an example to illustrate its coupling effect with the resin in the above-mentioned resin composition or the surface of the patterned film.

[0046] The alkoxy group -OR in Ti(OR)4 decomposes into -OH when it meets water (water can come from air or moisture released by the patterned film carrying the above resin composition under heating conditions). Under heating conditions, Ti-OH can form a chemical bond with -OH in the resin or -OH on the surface of the patterned film through dehydration condensation (such as through -Ti-O-bonding), or Ti-OH can form a chemical bond with -OH in the resin or -COOH on the surface of the patterned film (such as through -Ti-OC(=O)-bonding), so that the central atom Ti in the titanate can be used to achieve chemical bonding with the surface of the patterned film and the resin at the same time. In addition, since the resin and the surface of the patterned film are bridged by chemical bonds containing Ti atoms, the thickness of the above chemical thickening layer is relatively small, uniform and dense, which is conducive to obtaining a high-quality patterned film with moderate and uniform shrinkage of the pattern spacing.

[0047] In some embodiments of the present application, the coupling agent may further include orthosilicate. The chemical formula of orthosilicate may include Si(OR)4, and each R is independently selected from substituted or unsubstituted C 1-6The coupling mechanism of the orthosilicate can be found in the introduction of titanate Ti(OR)4 in the previous text of this application, except that the Ti atom is replaced by Si.

[0048] The substituents in the substituted alkyl group may include, but are not limited to, one or more of an alkoxy group, an aryl group, etc. The number of carbon atoms in the alkoxy group may be 1-6, for example, 1, 2, 3, 4, 5 or 6. The aryl group may be, for example, a phenyl group or a naphthyl group. In some possible embodiments, the substituted alkyl group may be a C 1-4 Alkoxy substituted C 1-6 In some embodiments, each R can be independently selected from one or more of ethyl, n-propyl, isopropyl, n-butyl, 2-methoxyethyl, and benzyl.

[0049] In some embodiments of the present application, in the above-mentioned resin composition, the total mass proportion of the coupling agent and the resin is 0.5-5wt%. The resin composition has a suitable solid content, which can ensure that after being coated on the patterned film, the pattern gap of the patterned film can be filled and thickened by 10-30%, so that after heat treatment, the pattern side wall of the patterned film can be effectively thickened and the pattern gap can be appropriately shrunk, and the patterned film will not be wasted due to the limited degree of thickening required for the patterned film, or it will cause difficulty in removal. Specifically, in the resin composition, the total mass proportion of the coupling agent and the resin can be 0.8wt%, 1wt%, 1.5wt%, 2wt%, 2.5wt%, 3wt%, 3.5wt%, 4wt%, 4.5wt% or 4.8wt%, etc.

[0050] In the present application, the side chain of the first repeating unit has a hydroxyl group and / or a carboxyl group, and the side chain of the second repeating unit does not contain a hydroxyl group or a carboxyl group. In some embodiments of the present application, the molar proportion of the first repeating unit having at least one of a hydroxyl group and a carboxyl group in the side chain of the resin is 30%-80%. Controlling the molar proportion of the first repeating unit containing a hydroxyl group and / or a carboxyl group in the resin within a suitable range is conducive to controlling the resin to have a suitably high solubility in a non-aqueous organic solvent (such as an alcohol solvent, and / or an ether solvent), ensuring that the resin composition is not prone to precipitation and is easy to apply; it is also conducive to controlling the resin and the above-mentioned small molecule coupling agent to have an appropriate degree of reaction part to ensure that the above-mentioned patterned film can be effectively thickened. Specifically, the molar proportion of the first repeating unit in all repeating units of the resin can be, for example, 35%, 40%, 42%, 45%, 48%, 50%, 52%, 55%, 58%, 60%, 70%, 75% or 78%, etc.

[0051] In the present application, the structures of the first repeating unit and the second repeating unit of the above resin are not particularly limited. In some embodiments of the present application, the first repeating unit comprises the structure shown in the following formula (I-1) and / or formula (I-2):

[0052] (Ⅰ-1) (Ⅰ-2)

[0053] Wherein, R1 and R2 are independently selected from hydrogen atoms, halogen atoms, methyl groups or halogenated methyl groups; L1 is independently selected from single bonds, *-COO-, or *-CONH- each time it occurs, and the * end is connected to the main chain carbon atom of formula (Ⅰ-1); L2 is independently selected from *-COO-, or *-CONH- each time it occurs, and the * end is connected to the main chain carbon atom of formula (Ⅰ-2); Z is independently selected from at least one of -OH and -COOH each time it occurs; R3 includes a substituted alkyl group including at least one of -OH and -COOH as a substituent.

[0054] As mentioned above, the halogen atom may include one or more of fluorine, chlorine, bromine, and iodine. The halomethyl group may be a perhalomethyl group (i.e., a trihalomethyl group), or a partial halomethyl group. For example, the halomethyl group may be a trifluoromethyl group (-CF3). In some embodiments, R1 and R2 are independently selected from a hydrogen atom or a methyl group.

[0055] When L1 in formula (I-1) is a single bond, the benzene ring is directly connected to the main chain carbon atom of (I-1). In this case, the structure shown in formula (I-1) is specifically a styrene repeating unit having at least one of a hydroxyl group (-OH) and a carboxyl group (-COOH) on the benzene ring. When L1 in formula (I-1) is *-COO-, the structure shown in formula (I-1) is specifically an aryl acrylate repeating unit having at least one of a hydroxyl group and a carboxyl group on the benzene ring. When L1 in formula (I-1) is *-CONH-, the structure shown in formula (I-1) is specifically an aromatic acrylamide repeating unit having at least one of a hydroxyl group and a carboxyl group on the benzene ring.

[0056] In formula (I-1), the hydroxyl group or carboxyl group may be directly connected to the benzene ring (that is, Z is -OH or -COOH), or may be indirectly connected to the benzene ring through other groups (such as alkylene). For the latter case, in some embodiments, that is, corresponding to the above Z is a substituted alkyl group whose substituent includes at least one of -OH and -COOH. Wherein, the number of carbon atoms of the substituted alkyl group may be 1-6, specifically 1, 2, 3, 4, 5 or 6. In addition, the substituted alkyl group may also have other substituents other than -OH or -COOH, which is not limited in this application. Wherein, the substituted alkyl group may contain or not contain a heteroatom linking group. The heteroatom linking group may include but is limited to an ether bond (-O-), a thioether bond (-S-), a carbonyl group (-CO-), -C(=O)-O-, or -OC(=O)-. The heteroatom linking group may be inserted between some carbon atoms in the alkyl group or connected to a carbon atom at one end of the alkyl group. Illustratively, Z can be -CH2CH2COOH, -CH2CH2OH, -C(CH3)2-OH, -C(CF3)2-OH, -OCH2CH2OH, -CH2CH2OCH2OH, and the like.

[0057] When L2 in formula (Ⅰ-2) is *-COO-, the structure shown in formula (Ⅰ-2) is specifically an alkyl acrylate repeating unit having at least one of a hydroxyl group and a carboxyl group in the side chain; when L2 in formula (Ⅰ-2) is *-CONH-, the structure shown in formula (Ⅰ-2) is an aliphatic acrylamide repeating unit having at least one of a hydroxyl group and a carboxyl group in the side chain.

[0058] R3 includes a substituted alkyl group including at least one of -OH and -COOH as a substituent. Wherein, -OH or -COOH can replace any hydrogen atom in the alkyl group (in this case, -OH or -COOH can be directly connected to a carbon atom in the alkyl group), or can be connected to a carbon atom in the alkyl group in the form of an aryl group substituted by -OH and / or -COOH. Wherein, the number of carbon atoms of the substituted alkyl group can be 1-6, and further can be 1-4. As described above, the substituted alkyl group can also have other substituents other than -OH or -COOH. Exemplarily, R3 can be -CH2CH2OH, or -CH2CH2-Ph-OH.

[0059] In some embodiments of the present application, the second repeating unit includes one or more repeating units derived from styrene-based substances, alkyl acrylates, and alkyl methacrylates that do not contain hydroxyl groups and carboxyl groups. That is, the second repeating unit includes at least one of styrene-based repeating units, alkyl acrylate repeating units, and alkyl methacrylate repeating units that do not contain hydroxyl groups and carboxyl groups. Among them, the styrene-based substance can be styrene, or a substituted styrene that does not contain hydroxyl groups and carboxyl groups on the benzene ring. Similarly, the alkyl group in alkyl acrylates and alkyl methacrylates can be an unsubstituted alkyl group, or a substituted alkyl group that does not contain hydroxyl groups and carboxyl groups.

[0060] In some embodiments of the present application, the weight average molecular weight M of the above resin is w In the range of 1000-20000. Control the M of the resin that can react with the coupling agent w In an appropriate range, it can be ensured that the number of the first repeating units in the resin that can be chemically bonded with the coupling agent is not too small, which is conducive to ensuring that the resin composition can effectively thicken the patterned film, and at the same time will not be affected by the M of the resin. w Too large will result in low solubility of the resin in the above resin composition. w It can be measured by Gel Permeation Chromatography (GPC) using polystyrene as a standard.

[0061] Exemplarily, the M of the resin w 2000, 3000, 4000, 4500, 5000, 5500, 6000, 6500, 7000, 7500, 8000, 8500, 9000, 9500, 10000, 12000, 15000, 18000 or 19000, etc. In some possible embodiments, the weight average molecular weight M of the resin is w In the range of 4000-10000, this is more conducive to the resin having good solubility in non-aqueous organic solvents and having a moderately obvious thickening effect on the patterned film.

[0062] In the present application, the solvent in the above-mentioned resin composition is a non-aqueous organic solvent to prevent the organic groups (such as substituted or unsubstituted alkoxy groups) in the molecular structure of the above-mentioned coupling agent from being hydrolyzed before the resin composition is coated on the surface of the patterned film, thereby precipitating solid particles and affecting the film-forming effect.

[0063] In the embodiment of the present application, the non-aqueous organic solvent in the above-mentioned resin composition may include one or more of an alcohol solvent and an ether solvent. These solvents are more conducive to the above-mentioned coupling agent and the resin with a reactive group that can act on the coupling agent to be dissolved therein, and it is not easy to dissolve the patterned film in contact with the resin composition. Among them, the alcohol solvent includes one or more of methanol, ethanol, n-propanol, isopropanol, n-butanol, sec-butanol, 4-methyl-2-pentanol, etc. The ether solvent may include one or more of n-butyl ether, diisoamyl ether, dipropylene glycol dimethyl ether, etc.

[0064] The embodiments of the present application also provide the use of the above-mentioned resin composition of the embodiments of the present application in reducing the critical dimension of a pattern.

[0065] The application is specifically to reduce the pattern spacing of the patterned film (specifically the photoresist pattern) during the manufacturing process of the semiconductor device. It can also be said that the resin composition is specifically used as a pattern shrinking material. With the patterned film with reduced pattern spacing, a functional layer pattern with smaller critical dimensions and higher resolution can be obtained, thereby obtaining a semiconductor device with a higher degree of integration.

[0066] In the semiconductor manufacturing process, the above resin composition can be used as a pattern shrinking material, which is arranged on the surface of a patterned film formed by a patterning process on a substrate. After heating, a part of the resin composition material near the interface of the patterned film reacts with the surface of the patterned film to form a chemical thickening layer, thereby increasing the thickness and width of the pattern. After removing the unreacted resin composition material, a fine patterned film with a smaller pattern spacing than the initial patterned film is formed. For details, please refer to the present application Figure 1 A schematic diagram showing the use of the resin composition of the present application to reduce the pattern spacing of a patterned film.

[0067] Wherein, for a patterned film having a contact hole pattern, the reduction of the critical dimension may refer to the reduction of the hole diameter. For a patterned film having a line pattern, the reduction of the critical dimension may refer to the reduction of the line spacing.

[0068] The embodiment of the present application also provides a method for manufacturing a semiconductor device. The method for manufacturing a semiconductor device may include the following steps S01, S02, and S03.

[0069] Step S01, such as Figure 1 As shown in (a), a substrate 10 having a patterned film 20 on its surface is provided, and the surface of the patterned film 20 has at least one of a hydroxyl group and a carboxyl group.

[0070] In the embodiment of the present application, the patterned film 20 is formed by a patterning process, and the patterning process generally includes steps such as coating a patterned composition, exposure, baking, and development. The patterned film 20 can be formed by a patterning technique with an exposure wavelength ≤ 1 9 3 nm (such as ArF lithography, etc.). The resolution of the patterned film 20 formed by these patterning techniques is already high, and it is more meaningful to perform graphic miniaturization on it. A patterned film with a smaller critical dimension can be obtained at a lower cost without replacing expensive new exposure equipment. Optionally, the thickness of the patterned film 20 formed by these patterning techniques is in the range of 20nm-200nm. This can ensure that the graphics have a suitable aspect ratio and are not prone to collapse.

[0071] In some embodiments of the present application, the patterned film 20 may be a photoresist pattern, and may further be a chemically amplified photoresist pattern. The chemically amplified photoresist may include a base resin and a photoacid generator. Since the patterned film 20 is a film having a certain pattern formed by a patterning process (that is, the chemically amplified photoresist has been exposed and developed, and the acid-labile groups have been deprotected in the exposed area), the surface of the patterned film 20 may have carboxyl groups (-COOH) or hydroxyl groups (-OH), with carboxyl groups being the majority. In addition, in some cases, the surface of the patterned film 20 may also have hydroxyl groups derived from other repeating units in the base resin other than the acid-labile repeating units.

[0072] The substrate 10 can be selected according to specific needs, for example, it can be a silicon wafer, or a silicon wafer covered by other coatings. The coatings can include one or more of an anti-reflective coating, an epitaxial layer, a metal layer, a dielectric layer (such as SiO2, or Si3N4), etc.

[0073] Step S02, such as Figure 1 As shown in (b), the resin composition of the embodiment of the present application is coated on the surface of the patterned film 20 to form a resin film 30, and then heated to react with the portion of the resin film 30 that contacts the patterned film 20.

[0074] Wherein, the coating method includes but is not limited to spin coating, dip coating, brush coating, etc. In the above-mentioned coating process, the above-mentioned resin composition is not only located on the surface of the patterned film 20, but also located in the pattern gap of the patterned film 20. Wherein, the thickness of the resin film 30 is preferably to fill the pattern gap (including pores) of the patterned film 20 and thicken by 10-30%. This is conducive to ensuring the formation of a chemical thickening layer of appropriate thickness, while not affecting the convenient removal of unreacted resin composition materials. Wherein, the coating thickness of the resin film 30 can be adjusted according to the amount of solvent added to the resin composition. Generally, the higher the solid content of the above-mentioned resin composition, the thicker the thickness of the resin film 30 formed by coating. Optionally, the solid content in the above-mentioned resin composition is 0.5-5wt%. While being able to effectively thicken the graphic sidewalls of the patterned film 20, it will not cause material waste.

[0075] In step S02, the heating may be heating the substrate 10 with the patterned film 20 and the resin film 30. During the heating process, a reaction occurs between the patterned film 20 and the resin film 30 at the contact interface. Figure 1 As shown in (c), a chemical thickening layer 40 of a certain thickness is formed on the surface of the patterned film 20. The chemical thickening layer 40 is mainly formed by chemically bridging the resin in the resin film 30 and the surface of the patterned film 20 with the help of the small molecule coupling agent in the resin film 30 under heating conditions. The formation mechanism of the chemical thickening layer 40 can be found in the explanation of the previous text of this application.

[0076] In the embodiment of the present application, the heating temperature may be 100-180°C, for example, 110°C, 120°C, 130°C, 150°C, 160°C, or 170°C. The heating time may be 30 seconds to 180 seconds, for example, 45s, 60s, 90s, 120s, etc. Controlling the heating temperature may control the reaction rate of the coupling agent in the resin film 30 with the surface active groups of the patterned film 20 and the resin in the resin film 30, thereby controlling the thickness of the chemical thickening layer 40 and the amount of pattern shrinkage. Controlling the heating time may also control the thickness of the chemical thickening layer 40.

[0077] Step S03, after removing the unreacted resin film 30 with a cleaning solution, a fine patterned film 20' with reduced pattern spacing is obtained on the substrate 10, such as Figure 1 As shown in (d).

[0078] The above-mentioned "unreacted resin film 30" specifically refers to the resin film 30 that is not grafted to the surface of the patterned film 20. This part of the resin film can be washed away by the cleaning solution, while the part of the resin film grafted to the surface of the patterned film 20 (i.e., the chemical thickening layer 40) can be retained without being washed away by the cleaning solution. Among them, the fine patterned film 20' can include the initial patterned film 20 and the chemical thickening layer 40 connected thereto. The presence of the chemical thickening layer 40 increases the thickness and pattern width of the fine patterned film 20', so that the interval between adjacent patterns of the fine patterned film 20' becomes smaller.

[0079] In the embodiment of the present application, the cleaning liquid may include an alkaline aqueous solution or an organic solvent. The cleaning liquid may be applied to the substrate 10 by spin coating, spraying, dipping, etc. Among them, the alkali in the alkaline aqueous solution may include one or more of tetramethylammonium hydroxide (TMAH), tetraethylammonium hydroxide (TEAH), tetrapropylammonium hydroxide (TPAH), tetrabutylammonium hydroxide (TBAH), etc. The organic solvent may include, but is not limited to, one or more of alcohol solvents (such as ethanol, isopropanol, ethylene glycol, propylene glycol, 1-pentanol, 4-methyl-2-pentanol, etc.), ester solvents (such as n-butyl acetate, propylene glycol monomethyl ether acetate, ethyl acetate, ethyl lactate, butyrolactone, etc.), ether solvents (such as propylene glycol monomethyl ether, propylene glycol ethyl ether, n-butyl ether, diisoamyl ether, dipropylene glycol dimethyl ether, anisole, etc.). The patterned film 20 formed by the patterning process has strong tolerance to these cleaning liquids, and when they are used to remove the unreacted resin film 30, the patterned film 20 below will not be damaged.

[0080] Optionally, the pattern pitch of the fine patterned film 20' in step S03 is reduced by 3-15 nm compared to the pattern pitch of the patterned film 20 in step S01. Figure 1 That is, Δd' is 3-15nm smaller than Δd. That is, the resin composition provided by the present application can reduce the pattern spacing of the patterned film 20 by 3-15nm. For the patterned film 20 with a higher pattern resolution, the pattern spacing of the patterned film 20 shrinks appropriately, and the adhesion of adjacent patterns will not occur.

[0081] After the above step S03, a fine patterned film 20' is formed on the substrate 10. The narrower pattern spacing of the fine patterned film 20' can be used to define smaller features than when only the patterned film 20 is used. In some embodiments, the pattern of the fine patterned film 20' can be transferred to the substrate to obtain a patterned substrate. The patterned substrate can be used in the manufacture of semiconductor devices such as chips to improve the manufacturing accuracy and quality of the devices.

[0082] After the above step S03, other functional layers can be prepared. For example, after the above step S03, a metal material can be deposited in the gap to form a metal pattern layer. The fine patterned film 20' with a narrower gap can also be used as a mask to perform high-precision etching on the substrate 10, and the pattern thereon can be transferred to the substrate 10 by etching to further realize the preparation of other coatings.

[0083] The manufacturing method of the above-mentioned semiconductor device provided in the embodiment of the present application, by adopting the resin composition of the embodiment of the present application as the pattern shrinkage material, can achieve a moderate reduction in the pattern spacing distance of the formed patterned film, obtain a fine pattern with a smaller critical dimension at a lower cost, and ensure that the obtained pattern has high clarity and small defects, which is conducive to the high-integration and high-precision development of semiconductor processes.

[0084] The embodiment of the present application also provides a semiconductor device, which is manufactured using the above-mentioned semiconductor manufacturing method of the embodiment of the present application.

[0085] The semiconductor device may include but is not limited to a chip, etc. It is understandable that the semiconductor device product usually does not contain the fine patterned film 20'.

[0086] The embodiments of the present application are further described below with reference to a plurality of embodiments.

[0087] Example 1

[0088] (I) Preparation of resin:

[0089] 8.00 g of N-p-hydroxyphenyl acrylamide, 4.94 g of 4-tert-butoxystyrene and 2.42 g of initiator dimethyl azobisisobutyrate were dissolved in 46 g of isopropanol solvent, and the oxygen in the system was removed by three freeze-thaw cycles, and then reacted at a reflux temperature of 83°C for 6 hours. The obtained reactant was vacuum dried to remove the solvent, 46 g of ethyl acetate was added and stirred to dissolve, and then 5 times the volume of n-heptane was added for precipitation. After suction filtration, the precipitation operation was repeated once, and the solid was collected. The obtained solid was vacuum dried at 60°C to obtain a weight average molecular weight M w The resin P1 has a molecular weight of 5808 and a molecular weight distribution index PDI of 2.45.

[0090] The preparation process of resin P1 is as follows:

[0091]

[0092] From the hydrogen nuclear magnetic resonance spectrum of the resin P1, it was found that the molar ratio of the repeating unit derived from N-p-hydroxyphenylacrylamide to the repeating unit derived from 4-tert-butoxystyrene (ie, m:n) was 3:2.

[0093] (II) Preparation of resin composition:

[0094] 2.6 g of resin P1 was dissolved in 97 g of n-butanol, and 0.4 g of tetraisopropyl titanate was added to the resulting solution. After sufficient stirring to dissolve, the solution was filtered through a polytetrafluoroethylene filter with a pore size of 0.22 μm to obtain a resin composition solution, which was recorded as F1.

[0095] (III) Preparation of pattern template 1:

[0096] The bottom anti-reflective coating material is coated on a silicon wafer substrate and heated on a hot plate at 205°C for 60 seconds to form a 30nm thick bottom anti-reflective coating. Then, a chemically amplified photoresist is coated on the bottom anti-reflective coating and heated on a hot plate at 110°C for 60 seconds to form a 120nm thick photoresist film layer. The photoresist film layer is exposed through a mask using an ArF exposure device, and baked on a hot plate at 95°C for 60 seconds after exposure. Thereafter, an aqueous solution of tetramethylammonium hydroxide with a concentration of 2.38wt% is used for immersion development for 60 seconds to remove the exposed portion, and then washed with deionized water for 10 seconds to form a hexagonally arranged contact hole pattern template P-CH (which can be referred to as pattern template 1) with a pore size of 130.44nm and a pore spacing of 345nm. The scanning electron microscope top view is shown as follows Figure 2 As shown in (a).

[0097] (IV) Resin composition for graphic miniaturization:

[0098] The resin composition F1 is spin-coated onto the contact hole pattern template P-CH at a speed of 1500 rpm to form a resin film, and heated on hot plates at 100°C, 120°C, and 150°C for 60 seconds, respectively, to react with the portion of the resin film in contact with the surface of the pattern template. Then, it is immersed in a tetramethylammonium hydroxide aqueous solution with a concentration of 2.38wt% for 30 seconds to remove the resin film material not connected to the surface of the graphic film, and washed in water for 10 seconds to obtain a contact hole pattern after the aperture is shrunk. The top views of the contact hole pattern after the aperture is shrunk obtained by heating at 100°C, 120°C, and 150°C are shown in FIG. Figure 2 The average pore size, pore size standard deviation, and pore size shrinkage of the contact hole patterns were measured from these figures, and the results are summarized in Table 1 below.

[0099] Comparative Example 1

[0100] Preparation of the resin composition: 2.6 g of resin P1 was dissolved in 97 g of n-butanol, and 0.4 g of a commercial crosslinking agent (methylated hexahydroxymethyl melamine resin) was added. After sufficient stirring to dissolve, the mixture was filtered through a polytetrafluoroethylene filter with a pore size of 0.22 μm to obtain a resin composition solution.

[0101] The resin composition provided in Comparative Example 1 was coated on the contact hole pattern template PCH, and heated on a hot plate at 150° C. for 60 seconds, then immersed in a 2.38wt% tetramethylammonium hydroxide aqueous solution for 30 seconds to remove materials not connected to the surface of the contact hole pattern template, and then washed in water for 10 seconds to obtain a top view of the contact hole pattern with a shrunken aperture under a scanning electron microscope as shown in FIG. Figure 2 The average pore size, pore size standard deviation and pore size shrinkage of the contact hole pattern were measured, and the results are also shown in Table 1 below.

[0102] Table 1

[0103]

[0104] Note: The pore size shrinkage refers to the difference between the average pore size of the contact holes obtained after the resin composition undergoes pattern shrinkage and the average pore size in the initial contact hole pattern template.

[0105] It can be seen from Table 1 that after the contact hole pattern template was subjected to pattern shrinkage using the resin composition F1 of Example 1 at heating temperatures of 100°C, 120°C, and 150°C, the average pore size shrinkage of the contact holes was 11.48nm, 6.16nm, and 3.85nm, respectively, which is much smaller than the pore size shrinkage caused by the resin composition of Comparative Example 1 using a polymer resin as a cross-linking agent, greatly reducing the probability of deformation of the contact hole shape. In addition, the pore size standard deviation of the contact holes in the contact hole pattern obtained by using the resin composition of Example 1 is also lower than that of Comparative Example 1, which can indicate that the pore size uniformity is also improved.

[0106] Example 2

[0107] (I) Preparation of resin:

[0108] 8.00 g of hydroquinone monomethacrylate, 4.87 g of 4-tert-butoxystyrene and 2.23 g of dimethyl azobisisobutyrate were dissolved in 46 g of isopropanol solvent, and the oxygen in the system was removed by three freeze-thaw cycles, and then the reaction was carried out at a reflux temperature of 83 ° C for 6 hours. After the obtained reactant was vacuum dried to remove the solvent, 46 g of ethyl acetate was added and stirred to dissolve, and then 5 times the volume of n-heptane was added for precipitation. After suction filtration, the precipitation operation was repeated once, and the solid was collected. The obtained solid was vacuum dried at 60 ° C to obtain a weight average molecular weight M wThe resin P2 has a molecular weight of 7025 and a molecular weight distribution index PDI of 2.25. According to the nuclear magnetic resonance test, the molar ratio of the repeating unit derived from hydroquinone monomethacrylate to the repeating unit derived from 4-tert-butoxystyrene in the resin P2 is 3:2.

[0109] The preparation process of resin P2 is as follows:

[0110]

[0111] (II) Preparation of resin composition:

[0112] 2.6 g of resin P2 was dissolved in 97 g of n-butanol, and 0.4 g of tetraisopropyl titanate was added to the resulting solution. After sufficient stirring to dissolve, the solution was filtered through a polytetrafluoroethylene filter with a pore size of 0.22 μm to obtain a resin composition solution, which was recorded as F2.

[0113] (III) Preparation of pattern template 2:

[0114] The bottom anti-reflective coating material is coated on a silicon wafer substrate and heated on a hot plate at 205°C for 60 seconds to form a 30nm thick bottom anti-reflective coating. Then, a chemically amplified photoresist is coated on the bottom anti-reflective coating and heated on a hot plate at 90°C for 60 seconds to form a 90nm thick photoresist film layer. The photoresist film layer is exposed through a mask using an ArF exposure device, and baked on a hot plate at 95°C for 60 seconds after exposure. After that, it is immersed in n-butyl acetate for 30 seconds to remove the exposed part, and washed with deionized water for 10 seconds to obtain a line pattern template N-LS (referred to as pattern template 2) with a line width of 54.66nm and a spacing of 125nm. The scanning electron microscope top view of the line pattern template is shown as follows. Figure 3 As shown in (a).

[0115] (IV) Resin composition for graphic miniaturization:

[0116] The resin composition F2 was spin-coated onto the line pattern template N-LS at a speed of 1500 rpm to form a resin film, and heated on hot plates at 100°C, 120°C, and 135°C for 60 seconds, respectively, to react with the portion of the resin film in contact with the surface of the pattern template. Then, the resin film was immersed in ethanol for 30 seconds to remove the resin film material not connected to the surface of the graphic film, thereby obtaining a line pattern with shrunk line spacing. The scanning electron microscope top views of the line pattern with shrunk line spacing obtained by heating at 100°C, 120°C, and 135°C are shown in FIG. Figure 3 The line width and line spacing shrinkage of the pattern were measured from these figures, and the results are summarized in Table 2 below.

[0117] Table 2

[0118]

[0119] It can be seen from Table 2 that after the line pattern template was subjected to graphic shrinkage using the resin composition F2 of Example 2 at heating temperatures of 100°C, 120°C, and 135°C, the graphic line width was appropriately increased and the line spacing was appropriately shrunk accordingly, with the line spacing shrinkage amounts being 6.66nm, 6.01nm, and 7.66nm, respectively.

[0120] Example 3

[0121] A resin composition, which is different from the resin composition F1 in Example 1 in that 0.4 g of tetraisopropyl titanate is replaced by 0.4 g of tetrabutyl zirconate.

[0122] Example 4

[0123] A resin composition, which is different from the resin composition F1 in Example 1 in that 0.4 g of tetraisopropyl titanate in Example 1 is replaced by 0.2 g of isopropyl titanate and 0.2 g of tetraethyl orthosilicate.

[0124] Referring to the method described in the above-mentioned Example 1, the resin compositions provided in Examples 3 and 4 were respectively coated on the contact hole pattern template PCH, and heated on a hot plate at 120°C for 60 seconds, and then immersed in a 2.38wt% tetramethylammonium hydroxide aqueous solution for 30 seconds to remove the resin composition material not connected to the surface of the pattern template, and then washed in water for 10 seconds to obtain a contact hole pattern with pore size shrinkage, and the average pore size, pore size standard deviation and pore size shrinkage amount were measured. The results are summarized in the following Table 3.

[0125] Table 3

[0126]

[0127] It can be seen from Table 3 that the resin composition of Example 3 using tetrabutyl zirconate as a coupling agent, or the resin composition of Example 4 using isopropyl titanate and orthosilicate as coupling agents at the same time, can also play a role in appropriately shrinking the aperture of the contact hole pattern. The shrinkage amount is about 6nm, which is much smaller than the aperture shrinkage amount caused by the resin composition of Comparative Example 1 using a polymer resin as a cross-linking agent, and the aperture uniformity of the shrunk contact holes is also high (reflected by a lower aperture standard deviation).

[0128] Example 5

[0129] Preparation of the resin composition: 2.8 g of resin P1 was dissolved in 97 g of n-butanol, and 0.2 g of tetraisopropyl titanate was added. After sufficient stirring and dissolution, the mixture was filtered through a polytetrafluoroethylene filter with a pore size of 0.22 μm to obtain a resin composition.

[0130] The resin composition provided in Example 5 was applied to the contact hole pattern template PCH, and heated on a hot plate at 120°C for 60 seconds, then immersed in a 2.38wt% tetramethylammonium hydroxide aqueous solution for 30 seconds to remove materials not connected to the pattern template surface, and then washed in water for 10 seconds to obtain a contact hole pattern with shrunken aperture. It was measured that the average aperture of the contact hole pattern was 126.64nm, the aperture standard deviation was 4.15nm, and the aperture shrinkage was 3.80nm.

[0131] Example 6

[0132] Preparation of the resin composition: 2.4 g of resin P1 was dissolved in 97 g of n-butanol, and 0.6 g of tetraisopropyl titanate was added. After sufficient stirring and dissolution, the mixture was filtered through a polytetrafluoroethylene filter with a pore size of 0.22 μm to obtain a resin composition.

[0133] The resin composition provided in Example 6 was applied to the contact hole pattern template PCH, and heated on a hot plate at 120°C for 60 seconds, then immersed in a 2.38wt% tetramethylammonium hydroxide aqueous solution for 30 seconds to remove materials not connected to the pattern template surface, and then washed in water for 10 seconds to obtain a contact hole pattern with shrunken aperture. It was measured that the average aperture of the contact hole pattern was 118.33nm, the aperture standard deviation was 4.01nm, and the aperture shrinkage was 12.11nm.

[0134] From the comparison among Examples 1, 5 and 6, it can be known that, when the solid content of the resin composition remains unchanged, the relative content of the coupling agent and the resin can be changed to achieve the regulation of the shrinkage amount of the aperture in the contact hole pattern.

[0135] Example 7

[0136] Preparation of the resin composition: 4.35 g of resin P1 was dissolved in 95 g of n-butanol, and 0.65 g of tetraisopropyl titanate was added. After sufficient stirring and dissolution, the mixture was filtered through a polytetrafluoroethylene filter with a pore size of 0.22 μm to obtain a resin composition.

[0137] The resin composition provided in Example 7 was applied to the contact hole pattern template PCH, and heated on a hot plate at 120°C for 60 seconds, then immersed in a 2.38wt% tetramethylammonium hydroxide aqueous solution for 30 seconds to remove materials not connected to the pattern template surface, and then washed in water for 10 seconds to obtain a contact hole pattern with shrunken aperture. It was measured that the average aperture of the contact hole pattern was 123.66nm, the aperture standard deviation was 3.11nm, and the aperture shrinkage was 6.78nm.

[0138] Example 8

[0139] A resin composition, which differs from the resin composition F1 of Example 1 in that the amounts of monomers used in preparing the resin are changed so that in the obtained resin, the molar ratio of repeating units derived from N-p-hydroxyphenylacrylamide to repeating units derived from 4-tert-butoxystyrene is 3:7.

[0140] Example 9

[0141] A resin composition, which differs from the resin composition F1 of Example 1 in that the amounts of monomers used in preparing the resin are changed so that in the obtained resin, the molar ratio of repeating units derived from N-p-hydroxyphenylacrylamide to repeating units derived from 4-tert-butoxystyrene is 8:2.

[0142] Table 4 below summarizes the test results of the resin compositions of Examples 8-9 and Example 1 for the pore size shrinkage of the contact hole pattern template PCH.

[0143] Table 4

[0144]

[0145] It can be seen from Table 4 that when the solid content and coupling agent in the resin composition remain unchanged, changing the molar ratio of the active repeating units of the resin in the resin composition of the embodiment of the present application within a certain range can also have the effect of appropriately and uniformly shrinking the pore size in the contact hole pattern.

[0146] The above only expresses the exemplary embodiments of the present application, and the description is relatively specific and detailed, but it cannot be understood as limiting the scope of the patent of the present application. It should be pointed out that for ordinary technicians in this field, several modifications and improvements can be made without departing from the concept of the present application, which all belong to the protection scope of the present application. Therefore, the protection scope of the patent of the present application shall be based on the attached claims.

[0147] It should be understood that the first, second and various numerical numbers involved in this document are only used for the convenience of description and are not used to limit the scope of this application. In this application, "and / or" describes the association relationship of associated objects, indicating that three relationships may exist. For example, A and / or B can represent: A exists alone, A and B exist at the same time, and B exists alone, where A and B can be singular or plural. The character " / " generally indicates that the associated objects before and after are in an "or" relationship.

[0148] In the description of this application, unless otherwise specified, the meaning of "multiple" refers to greater than or equal to two. "At least one" refers to one or more. "At least one of the following" or similar expressions refers to any combination of these items, including any combination of single or plural items. For example, "at least one of a, b, or c", or "at least one of a, b, and c" can all mean: a, b, c, ab (i.e., a and b), ac, bc, or abc, where a, b, and c can be single or multiple.

[0149] In addition, the numerical range represented by "-" in this application refers to the range that includes the numerical values ​​recorded before and after "-" as the minimum and maximum values, respectively. In this application, expressions about parameter ranges, such as "greater than or equal to (≥)", "less than or equal to (≤)", "above...", and "below..." all include the number itself. The numerical values ​​and numerical ranges involved in the embodiments of this application are approximate values. Due to the influence of manufacturing processes / testing methods, etc., there may be a certain range of errors, which can be considered negligible by those skilled in the art.

Claims

1. A resin composition for pattern size scaling of a patterned film, characterized in that: The resin composition comprises a resin, a coupling agent and a non-aqueous organic solvent, wherein the coupling agent comprises one or more of titanate, zirconate and aluminate, the resin comprises a first repeating unit having a side chain with a reactive group that can react with the coupling agent, and a second repeating unit having a side chain without the reactive group, the reactive group comprises a hydroxyl group and / or a carboxyl group, and the mass of the coupling agent is 1%-30% of the mass of the resin.

2. The resin composition according to claim 1, characterized in that The chemical formula of the titanate includes TiL4, the chemical formula of the zirconate includes ZrL4, and the chemical formula of the aluminate includes AlL3, each L being independently selected from C 2-8 One of an alkoxy group, a benzyloxy group, a triethanolamine group, an acetylacetonate group, and an ethyl acetoacetate group.

3. The resin composition according to claim 1, characterized in that The coupling agent also includes orthosilicate; wherein the chemical formula of the orthosilicate includes Si(OR)4, and each R is independently selected from one of methyl, ethyl, n-propyl, isopropyl, n-butyl, 2-methoxyethyl, and benzyl.

4. The resin composition according to claim 1, characterized in that In the resin composition, the total weight ratio of the coupling agent and the resin is 0.5wt%-5wt%.

5. The resin composition according to any one of claims 1 to 4, characterized in that The molar proportion of the first repeating unit in all repeating units of the resin is 30%-80%.

6. The resin composition according to claim 1, characterized in that The first repeating unit comprises the structure represented by the following formula (I-1) and / or formula (I-2): (Ⅰ-1) (Ⅰ-2) Wherein, R1 and R2 are independently selected from hydrogen atoms, halogen atoms, methyl groups or halogenated methyl groups; L1 is independently selected from single bonds, *-COO-, or *-CONH- each time it occurs, and the * end is connected to the main chain carbon atom of formula (Ⅰ-1); L2 is independently selected from *-COO-, or *-CONH- each time it occurs, and the * end is connected to the main chain carbon atom of formula (Ⅰ-2); Z includes at least one of -OH and -COOH; R3 includes a substituted alkyl group including at least one of -OH and -COOH.

7. The resin composition according to claim 1, characterized in that The second repeating unit includes one or more repeating units derived from styrene-based substances without hydroxyl groups and carboxyl groups, alkyl acrylates, and alkyl methacrylates.

8. The resin composition according to claim 1, characterized in that The weight average molecular weight of the resin is in the range of 1,000-20,000.

9. The resin composition according to claim 8, characterized in that The weight average molecular weight of the resin is in the range of 4,000-10,000.

10. The resin composition according to claim 1, characterized in that The non-aqueous organic solvent includes one or more of an alcohol solvent and an ether solvent.

11. The resin composition according to claim 10, characterized in that The alcohol solvent includes one or more of methanol, ethanol, n-propanol, isopropanol, n-butanol, sec-butanol, and 4-methyl-2-pentanol; the ether solvent includes one or more of n-butyl ether, diisoamyl ether, and dipropylene glycol dimethyl ether.

12. Use of the resin composition according to any one of claims 1 to 11 in reducing the critical dimension of a pattern.

13. A method for manufacturing a semiconductor device, characterized in that: include: (1) Providing a substrate having a patterned thin film on its surface; The surface of the patterned film has at least one of a hydroxyl group and a carboxyl group; (2) applying the resin composition according to any one of claims 1 to 11 to the surface of the patterned film to form a resin film, and heating the resin film to react with the portion of the resin film in contact with the patterned film; (3) The unreacted resin film is removed by a cleaning solution to obtain a fine patterned film with reduced pattern spacing on the substrate.

14. The manufacturing method according to claim 13, characterized in that: The pattern spacing of the fine patterned film in step (3) is 3-15 nm smaller than that of the patterned film in step (1).

15. A semiconductor device, characterized in that: The method is prepared by the method according to any one of claims 13 to 14.

Citation Information

Patent Citations

  • Optical film with excellent solvent resistance and polarizing plate comprising same

    CN105593706A

  • Pattern forming process and shrink agent

    US20160124313A1

  • Adhesive coating material

    US4533701A